PENGGUNAAN MEDIA VISUAL UNTUK MENINGKATKAN PEMAHAMAN KONSEP IRISAN BIDANG DENGAN BANGUN RUANG PADA SISWA KELAS X-A SMA NEGERI 8 KUPANG - Yosef Nurak (Program Studi Pendidikan Matematika, Universitas Muhammadiyah Kupang, 2020)
Mathematics is a subject that many students find difficult. This is because the abstract mathematical objects, so students are difficult to understand. Thus mathematics learning needs to be endeavored according to the cognitive abilities of students, to concrete abstract mathematical objects so that students can understand them easily. From the experience of researchers in teaching over the years, many students have difficulty understanding dimensional slices of a three especially to get up the field. For this reason, it is necessary to conduct research that aims to improve students' understanding of the concept of a slice of a field with a space structure, with the object of research being students of class X-A SMA Negeri 8 Kupang. The approach taken in this study is a qualitative approach using a classroom action research design. Implementation of the actions carried out in two cycles, the first cycle is the implementation of learning material slices of a field to get up the sketch with the media, and the second cycle of the implementation of learning material a wedge to get up the field with visual media or media-based power point presentation. The data in this study were obtained by observation, administration of questionnaires and tests to the object of research. The data obtained from observations and questionnaires were analyzed by means of qualitative analysis, while the data obtained from the tests were analyzed by means of quantitative analysis. The results showed that the students' mastery of a slice of a field with a space of >80% with an average final test result of 88.6 and 68% of students said that the use of visual media could improve their understanding in learning sliced fields with spatial shapes.